Copular alternation in Spanish and Catalan attributive sentences - Brucart, José María (Linguística: Revista de Estudos Linguísticos da Universidade do Porto, 2017)
This paper deals with copular selection in Spanish and Catalan attributive clauses. We develop an analysis of the copular alternation that is based on the relation of coincidence. Locative attributives, the class of copular sentences that has received less attention in the literature, are analyzed in detail. It is concluded that locative attributives express an abstract path; that is, a terminal coincidence relation between a figure (the entity that is located) and a ground (the location). The use of estar in these sentences is justified by the fact that this copula has an interpretable terminal coincidence feature that can license its uninterpretable counterpart in the attributive clause. Nevertheless, ser –the default copula– can also co-occur in locative attributives when the notion of bounded path is already incorporated in the entity that is being located. This is the case in Catalan, which uses a–a preposition that expresses a limit– instead of en –a central coincidence preposition. The copula ser also appears in the location of eventive entities and in path noun constructions. The terminal coincidence feature of estar can also superimpose a delimiting aspectual boundary to the attributive relation when there is no uninterpretable terminal coincidence feature to value in it. In these cases, evidential and sensorial readings are conveyed. Finally, a possible analysis is sketched for the differences in the selection of the copula between Spanish and Catalan with participles and perfective adjectives. It is suggested that the selection of estar in these cases may be due to the fact that both classes have a weaker functional structure in Spanish than in Catalan.